LEGISLATION CONCERNING NATIVE PROTECTION OF CERRADO VEGETATION IN THE CENTRAL WEST REGION (CIPEEX, 2022)
THIS SUMMARY WILL EMPHASIZE THE CERRADO BIOME, SINCE IT LACKS ENVIRONMENTAL NORMS AIMED AT ITS PRESERVATION. THIS SUMMARY SEEKS TO ASSESS WHETHER THE STATES OF THE CENTRAL-WEST REGION WITH OCCURRENCE OF NATIVE VEGETATION OF THE CERRADO BIOME HAVE NORMS THAT REGULATE THEIR PROTECTION AND PRESERVATION RESULTING FROM THE SUPPRESSION OF NATIVE VEGETATION. THEREFORE, WE PRESENT A DISCUSSION ON THE EVOLUTION OF ENVIRONMENTAL LEGISLATION IN THE CENTER-WEST REGION AIMED AT THE PRESERVATION AND CONSERVATION OF NATIVE VEGETATION OF THE CERRADO BIOME. AMONG THE STATES OF THE CENTRAL-WEST REGION, GOIS AND THE FEDERAL DISTRICT, HAVE THE SPECIFIC LEGISLATION THAT PROVIDES FOR THE CERRADO BIOME, BEING, THEREFORE, THE MOST ADEQUATE FOR THE PRESERVATION OF THE NATIVE VEGETATION OF THE CERRADO. THE LAWS OF THE STATE OF GOIS AND THE FEDERAL DISTRICT RECOGNIZE THE CERRADO BIOME AS A NATURAL HERITAGE, PROTECT THE NATIVE VEGETATION, IN ADDITION, APA'S WERE CREATED WITH SPECIFIC NORMS FOR THE PROTECTION AND PRESERVATION OF THE CERRADO'S PHYTOPHYSIOGNOMIES. WITH THE CONVERSION OF NATURAL AREAS INTO HUMAN ACTIVITIES, THE HIGH FRAGMENTATION OF THE REMAINING NATURAL HABITATS OF THE CERRADO WAS OBSERVED, WHICH INTERFERES WITH THE MAINTENANCE AND REPRODUCTION OF SPECIES AND THEIR CONSERVATION. ONE OF THE MECHANISMS THAT CAN HELP PROTECT BIODIVERSITY, HAVING THE ROLE OF CONSERVING AND PRESERVING NATURE, IS THE CREATION OF PROTECTED AREAS IN CONSERVATION UNITS (UCS). THE UCS ARE TERRITORIAL SPACES, WITH RELEVANT NATURAL CHARACTERISTICS, TO ENSURE THE MAINTENANCE OF ECOLOGICAL CONDITIONS AND GUARANTEE THE CONDITIONS FOR THE PERPETUATION OF ANIMAL AND PLANT SPECIES. IN THIS SENSE, THE CUS ENCOMPASSING THE ENVIRONMENTAL PROTECTION AREAS HAVE THE ROLE OF CONSERVING AND PRESERVING THE ENVIRONMENT. IN 2019, THE BRAZILIAN CERRADO HAD 8.21% OF ITS TERRITORY LEGALLY PROTECTED BY CONSERVATION UNITS, OF WHICH 2.85% CONSISTED OF INTEGRAL PROTECTION CONSERVATION UNITS, A QUANTITY THAT MAKES THE CERRADO THE BIOME WITH THE LOWEST PERCENTAGE OF AREAS UNDER INTEGRAL PROTECTION AMONG ALL THE WORLD'S HOTSPOTS.
Keywords: legislation; biodiversity; cerrado biome